Propagandowe wykorzystanie świąt i rocznic w okresie stalinowskim (1945–1956) na przykładzie regionu dolnośląskiego i częstochowskiego - Talarek, Adrian (In Gremium. Studies in History, Culture and Politics, 2020)
The holiday in the communist regime was a very specific space for constructing certain propaganda meanings, broadcast and received in the convention of free time and social recreation. This allows the organizers of these activities to focus more on recipient awareness than in other communication situations (propaganda activities carried out in the workplace). Organization of the holiday allows gathering a large number of participants and subjecting them to massive, thought-out intellectual and emotional manipulation. The universality of the holiday and its ability to shape positive social emotions is an invaluable opportunity for every government to capitalize on the political capital useful to it. For these reasons, the analysis of holidays implemented for public realization is a reliable platform for characterizing some methods of communist propaganda [1]. The canon of celebrating national holidays in People’s Poland was practically the same. The most important were: Labor Day, Polish Rebirth Day, Polish Army Day and the October Revolution Day. There were other smaller holidays but these were the most important and most celebrated. The topic of the article is to show how the Polish authorities used Stalinist ceremonies for propaganda purposes during the Stalinist period, on the example of two different regions.